The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c8ra07728b
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth for magnesia inclusion in Fe–O–Mg melt

Abstract: The crystallization process of magnesia involves two steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The details of the relationship among the thermodynamic properties, the atomic harmonic vibrational frequency and temperature can be found in the previous study. 23…”
Section: Dft Calculation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of the relationship among the thermodynamic properties, the atomic harmonic vibrational frequency and temperature can be found in the previous study. 23…”
Section: Dft Calculation Detailsmentioning
confidence: 99%
“…It was reported that there is a close relationship between the thermodynamic properties and the size of deoxidation product particles. 22,23 The products of metal deoxidation reaction in liquid iron in most case could be stable and metastable inclusions. 22,23 Therefore, the difference of thermodynamics for Cadeoxidation in liquid iron may be caused by the size effect of inclusion product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why the equilibrium constants obtained by various researchers are different to each other? Some researchers suggested that the thermodynamic properties of inclusions have a close relationship with its size [23][24][25][26][27]. Wasai et al [24] indicated that the interfacial free energy between nano-inclusions and liquid iron increased with the increasing of the inclusion size, and the Gibbs free energy change of deoxidation reaction has a close relationship with the size change of inclusion.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the researchers are focused on the thermodynamic equilibrium between the bulk-alumina and iron melt, while less known about the thermodynamic properties of nano-alumina in liquid iron. Many previous work proved that the thermodynamic properties of the nano-alumina are different from that of the bulk-alumina, and the thermodynamic difference among the nanoscale inclusions is more obvious with the decreasing size of inclusions [31][32][33][34][35][36][37][38] . It was reported that the interfacial free energy between nano-alumina and liquid iron are decreased with the decreasing of the size of alumina, and the Gibbs free energy change of Al-deoxidation reaction has very close relation with the size change of alumina inclusion 31 .…”
mentioning
confidence: 99%